BEHAVIOURAL ACCOUNTING: AN INTRODUCTION TO UNDERSTANDING - SALLY PAULINA SANDANAFU (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2023)
This paper will briefly discuss behavioural accounting. Pragmatically, behavioural accounting is the application of social science concepts to several accounting research areas such as budgeting, decision-making, controlling, and financial reporting. This newly emerging subdiscipline tries to focus on the human element with its human nature. Although accounting is essentially a quantitative field of study. The method of this study is a literature search, with the primary data sources being related scientific journals, and also other sources compatible with the theme of this discourse. This paper provides a brief introduction to behavioural accounting.